Does Previous Pelvic Osteotomy Compromise the Results of Periacetabular Osteotomy Surgery?. Issue 4 (April 2015) - Stambough, Jeffrey B.; Clohisy, John C.; Baca, Geneva R.; Zaltz, Ira; Trousdale, Robert; Millis, Michael; Sucato, Daniel; Kim, Young‐Jo; Sink, Ernest; Schoenecker, Perry L.; Sierra, Rafael; Podeszwa, David; et al.
Abstract: Background: As the Bernese periacetabular osteotomy (PAO) has grown in popularity, specific indications and the results in patients treated for those indications need to be evaluated. Currently, although many patients undergo PAO after having had prior pelvic osteotomy, there is limited information regarding the efficacy of the PAO in these patients. Questions/purposes: The purpose of this study was to compare the (1) early pain, function, activity, and quality of life outcomes; (2) radiographic correction; and (3) major complications and failures between patients who underwent PAO after prior pelvic reconstruction versus those who had a PAO without prior surgery. Methods: Between February 2008 and January 2012, 39 patients underwent PAO after prior pelvic osteotomy at one of 11 centers and were entered into a collaborative multicenter database. Of those, 34 (87%) were available for followup at a mean of 2.5 years (range 1‐5 years). This group was compared with a matched group of 78 subjects, of whom 71 (91%) were available for followup at a similar interval. We compared clinical outcomes including UCLA activity score, SF‐12, and Hip Disability and Osteoarthritis Outcome Score (HOOS); radiographic measures—anterior and lateral center‐edge angle and acetabular inclination (AI)—and reoperations, major complications, and conversions to total hip arthroplasty. Results: Although both groups reached clinical improvement in all categorical measures, the revision PAO group demonstrated greater pain (HOOS pain, study 74 versus 85, p = 0.03; 95% confidence interval [CI], 18.58 to −0.95) and less function (HOOS activities of daily living, study 80 versus 92, p = 0.002; 95% CI, 018.99‐4.45) than the primary cohort. The revision cohort achieved a smaller average radiographic correction than in patients undergoing PAO without prior pelvic surgery. The mean correction in AI was less dramatic when directly comparing the revision and comparison groups (−12° to −17°, p < 0.001, SD 2.3‐8.5). Although there was no difference in severe complications requiring further surgery, there were two conversions to hip arthroplasty (p = 0.109; 95% CI, 0.004‐2.042) in the study group. Conclusions: PAO performed after prior pelvic surgery is associated with improvements in pain, function, radiographic correction, and early complication rates, but the improvements observed at short‐term followup were smaller and more variable than those seen in patients who had not undergone prior pelvic surgery. We recommend considering PAO for residual deformities after prior osteotomy to improve function and quality life but warning patients of potential ceiling effects with a second periacetabular surgery. Level of Evidence: Level III, therapeutic study.